Students’ In-School Meal Experiences: A Study Of K - 5th Graders’ Level Of Satisfaction - Swaney-Stueve, Marianne; Elmore, Janelle; Hanson, Jennifer Ann (School Nutrition Association, 2020)
PURPOSE/OBJECTIVE To explore the relationships between grade level and students’ in-school meal experiences including school food service outcome measures and satisfaction with food from home. METHODS Outcomes were measured using an online survey conducted within one urban school district. Food selection was self-reported while a 7-point emoji facial scale was used to measure students’ satisfaction with their dining experience, school foods, and food brought from home. A convenience sample of 1942 elementary students was solicited among kindergarten to 5th grade students in nine schools. Cluster analysis on mean responses was used to classify grades into like groups. Analysis of variance was used to determine differences in mean values for each item by grade group. RESULTS Results show that grade level had a significant impact on mean satisfaction ratings. Two distinct grade groups were identified: kindergarten through 2nd grades and 3rd through 5th grades. As grade level increased from kindergarten to 5th grade, students selected a wider variety of entrees but their ratings indicated decreased satisfaction. One striking exception was noted, satisfaction with food brought from home became more positive with increasing grade level. APPLICATION TO CHILD NUTRITION PROFESSIONALS Findings from this study highlight the importance of obtaining feedback as evenly as possible across grades in an effort to ensure collected data reflects the opinions of the whole population. If even sampling is not achieved, nutrition programs striving to gather information from their student body can apply grade-level weighting factors to compensate for over- or under-sampling. Findings from this study also suggest that there are opportunities to improve satisfaction and possibly increase program participation with solicitation of feedback. Understanding grade level differences in food item selection and satisfaction can provide valuable insights for food service professionals planning menus and making procurement decisions for their operations. Furthermore, results suggest a better understanding of the phenomena surrounding students’ satisfaction with food brought from home is needed.
Keywords: Students; School food service; School lunch; Satisfaction; Elementary school; Developmental